Uncategorized

Solution: Solve for the value of x given three equations: 2x – y + z = 6, x- 3y – 2z = 13 and 2x – 3y – 3z = 16

Solve for the value of x given three equations: 2x – y + z = 6, x- 3y - 2z = 13 and 2x - 3y - 3z = 16

Problem Statement: EE Board October 1993

Solve for the value of x.

2x – y + z = 6
x – 3y – 2z = 13
2x – 3y – 3z = 16

  • A. 4
  • B. 3
  • C. 2
  • D. 1

Problem Answer:

The value of x is equal to 2.

Solution:

Latest Problem Solving in Fundamentals in Algebra

div.feedburnerFeedBlock ul li {background: #E2F0FD;
list-style-type: none;
margin:0 0 5px 0px;
padding:5px 5px 5px 10px !important;
border: 1px solid #0080ff;
border-radius:8px;
-moz-border-radius:8px;
-webkit-border-radius:8px;

}

div.feedburnerFeedBlock ul li:hover {
background:#ffffff;
}

div.feedburnerFeedBlock ul li a{
color:#ffffff;
text-decoration:none;
}

div.feedburnerFeedBlock ul li a:hover {
text-decoration: underline;
color: #000000;
}
div #creditfooter{
display: none;
}

More Questions in: Fundamentals in Algebra

Online Questions and Answers in Fundamentals in Algebra Series

Leave a Reply

Your email address will not be published. Required fields are marked *